2019
DOI: 10.1051/medsci/2019225
|View full text |Cite
|
Sign up to set email alerts
|

L’immunothérapie, une révolution en oncologie

Abstract: L’immunothérapie anti-tumorale représente un changement de paradigme majeur où le traitement ne cible plus directement les cellules tumorales mais le patient lui-même, afin de restaurer une immunité anti-tumorale efficace. Parmi les différentes immunothérapies, les inhibiteurs de points de contrôle immunitaire occupent une place centrale dans les options thérapeutiques disponibles de deux cancers au pronostic particulièrement péjoratif: le mélanome malin et le cancer pulmonaire non à petites cellules métastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Hao et al ’s meta-analysis of studies of immunotherapy in advanced melanoma reported that the risk ratio for an objective response (relative to chemotherapy) was 3.43 [5]. ICIs act by suppressing immune system inhibition and restoring anti-tumour activity [6]. The mechanism of action depends on the protein target: anti-cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) agents inhibit the interaction between antigen-presenting cells and T lymphocytes, whereas anti-programmed cell death-1 (PD-1) agents act on the downstream interaction between T lymphocytes and tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al ’s meta-analysis of studies of immunotherapy in advanced melanoma reported that the risk ratio for an objective response (relative to chemotherapy) was 3.43 [5]. ICIs act by suppressing immune system inhibition and restoring anti-tumour activity [6]. The mechanism of action depends on the protein target: anti-cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) agents inhibit the interaction between antigen-presenting cells and T lymphocytes, whereas anti-programmed cell death-1 (PD-1) agents act on the downstream interaction between T lymphocytes and tumor cells.…”
Section: Introductionmentioning
confidence: 99%